LncRNA EN-90756 promotes CPB2-induced proliferation and inhibits apoptosis in IPEC-J2 cells by affecting the JAK-STAT signaling pathway activation - Yang, Jiaojiao; Zhang, Juanli; Yang, Qiaoli; Huang, Xiaoyu; Yan, Zunqiang; Wang, Pengfei; Gao, Xiaoli; Li, Jie; Li, Na; Gao, Yi; Gun, Shuangbao (Frontiers in Microbiology, 2023)
Long non-coding RNAs (lncRNAs) are closely associated with the development of a variety of diseases as key regulators. However, there are few reports on the mechanisms of lncRNAs regulating Clostridium perfringens type C induced piglet diarrhoea. In the present study, we explored the expression and characterization of lncRNAs in CPB2 toxin-treated intestinal porcine epithelial cell line-J2 (IPEC-J2) using RNA-sequencing (RNA-seq) technology. A total of 6558 lncRNAs were identified, of which 49 lncRNAs were significantly differentially expressed in control and CPB2 groups. Functional enrichment analysis showed that the target genes of differentially expressed lncRNA EN-90756 were mainly associated with defense response to virus, negative regulation of apoptotic process. Simultaneously, we found that lncRNA EN-90756 was significantly up-regulated in IPEC-J2 cells at different time points after CPB2 treatment. Functionally, lncRNA EN-90756 knockdown inhibits proliferation and promotes apoptosis in IPEC-J2 cells by suppressing the JAK-STAT signaling pathway. LncRNA EN-90756 may be involved in CPB2 toxin-induced piglet diarrhoea by regulating the expression of target gene MX1. In summary, lncRNA EN-90756 enhanced the antiviral ability of IPEC-J2 cells by regulating the expression of MX1. Meanwhile, lncRNA EN-90756 could activate the JAK-STAT signaling pathway to regulate cell proliferation and apoptosis. These findings provide novel perspectives and directions for further exploration of the regulatory mechanisms of lncRNAs on CPB2 toxin-induced diarrhoea in piglets.